2022
DOI: 10.1177/13591053221134848
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of COVID-19 fear and psychological wellbeing in the United Kingdom

Abstract: The COVID-19 pandemic continues to impact global psychological wellbeing. To investigate the sustained impact of COVID-19 on wellbeing, the current study longitudinally assessed fear of COVID-19, anxiety, depression, intolerance of uncertainty, worry, sleep quality, loneliness and alcohol use during the pandemic in the United Kingdom. Timepoint 1 (T1; N = 445) took place in February 2021 following the highest number of pandemic-related deaths in the UK. Timepoint 2 (T2, N = 198) took place in June 2021 when pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Another longitudinal study conducted in Argentina reported an increase in the levels of depression, while symptoms of anxiety and both positive and negative affect showed a decrease over the first 2 weeks after the quarantine was imposed [ 14 ]. In the UK, the impact of fear of COVID-19 significantly decreased between the time of the highest number of pandemic-related deaths and the use of vaccine and subsequent decline of victims, which was separated by four months [ 15 ]. A recent systematic review and meta-analysis of longitudinal cohort studies on mental health problems before and during the pandemic concluded that psychological symptoms increased soon after the COVID-19 outbreak but then decreased to levels comparable to those in the prepandemic period [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another longitudinal study conducted in Argentina reported an increase in the levels of depression, while symptoms of anxiety and both positive and negative affect showed a decrease over the first 2 weeks after the quarantine was imposed [ 14 ]. In the UK, the impact of fear of COVID-19 significantly decreased between the time of the highest number of pandemic-related deaths and the use of vaccine and subsequent decline of victims, which was separated by four months [ 15 ]. A recent systematic review and meta-analysis of longitudinal cohort studies on mental health problems before and during the pandemic concluded that psychological symptoms increased soon after the COVID-19 outbreak but then decreased to levels comparable to those in the prepandemic period [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main function of fear is to protect an individual from an immediate known external danger (COVID-19, in this case) by eliciting the expression of a range of adaptive and defensive behaviors [ 20 ]. Exploring this emotional response in the specific context of COVID-19 is of paramount importance to understand the impact, not only on compliance with safety measures to contend with the spread of the disease but also on the adaptation process to this global health crisis (i.e., functional and adaptive versus irrational and pathological fear responses) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(15) Yet only a handful of longitudinal studies which report the level of COVID anxiety (or closely related concepts like coronaphobia, COVID Stress Disorder/Syndrome, COVID-19 fear, COVID-related worries, or COVID-19 anxiety syndrome) in the same people over time have been published, and none have examined which factors are predictive of a change in symptoms. (16,17,18,19) These studies ranged in their follow-up periods from between 5 and 14 months and cover a time period from February 2020 until July 2021 in China, Netherlands, United Kingdom and United States. Two studies assessed symptoms at more than 2 time-points.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have established the association between COVID-19 disruptions and worsening levels of anxiety, depression, loneliness, and worry [7][8][9][10]. Additionally, parents report higher levels of COVID-19 induced stress in comparison to adults without children, and these levels likely worsened with school closures [11,12].…”
Section: Introductionmentioning
confidence: 99%